Management of wild reindeer in Norway - Reimers, Eigil (Rangifer, 1986)
Wild reindeer in Norway are found in 26 separate management areas. Predators are virtually absent from all areas and hunting is the most important factor determining population development through alterations of herd size and structure. Average population density (animals/km2) after hunt was 1.96 in Hardangervidda, 1.18 in North Rondane and between 0.78 and 0.87 in Rondane South, Snøhetta, North Ottadalen and Forelhogna. Body size and female pregnancy rates followed a reverse trend. Average net increase of the herds varied from 42.2±10.0% in Forelhogna to 18.8±8.0% in Rondane North. In areas with animals in prime physical condition a high versus a low average harvest rate of calves resulted in a similar number of animals harvested, but a lower total yield of meat and revenue from hunting licences. At a winter population density of 0.8 - 2.0 animals/km2 annual harvest (per km2) of wild reindeer amounts to 0.23 - 0.51 animals, 9 - 18 kg meat and 286 - 850 NKr from sale of hunting licences. There was a significant relationship between body size expressed as carcass weights or mandible length and harvest success.